PTH-090 Survival after a diagnosis of hepatocellular carcinoma. (8th June 2018) - Driver, Robert; Chizhande, David; Jones, Rebecca; Rowe, Ian
Abstract : Introduction: Survival estimates for different Barcelona Clinic Liver Cancer (BCLC) stages in hepatocellular carcinoma (HCC) contained in the EASL-EORTC Clinical Practice Guidelines rely on outcomes from randomised control trials and meta-analysis of pooled data. To identify areas for development to facilitate improvements in outcomes we aimed to provide an insight into HCC survival outcomes outside a clinical trials setting by presenting a large experience of patients referred with HCC to a regional hepatobiliary cancer centre in the UK. Methods: All patients referred to the Hepatobiliary Cancer Multidisciplinary Team with a diagnosis of HCC over a two year period (January 2013 to December 2014) were included. Patients were stratified by their initial treatment modality according to the BCLC classification. Kaplan-Meier survival analysis was used to compare outcomes by initial treatment allocation. Results: Among 356 patients (median age 66 years, 291 (82%) male), the most frequent underlying disease aetiologies were hepatitis C and alcohol-related liver disease. Overall survival at 3 years after diagnosis was 38% and 146 patients (41%) received treatment with curative intent. The 3 year survival for liver transplant was 84% (56 patients) and for resection it was 89% (46 patients). The median survival for radiofrequency ablation was 45 months (44 patients) and for trans-arterial chemoembolization (TACE) it was 18 months (72 patients). For patients receiving sorafenib as first-line therapy, the median survival was 9.6 months (12 patients) and for those receiving best supportive care (BSC) it was 3.4 months (126 patients). Conclusions: These estimates of overall survival are consistent with those published in the EASL-EORTC Clinical Practice Guidelines and demonstrate that these figures give a reliable estimate of overall survival in a real-world experience. Over one third of patients were unsuitable for anti-cancer therapy at presentation and only a minority received treatment with curative intent. This highlights areas for potential improvement in outcomes particularly through early diagnosis of cirrhosis, facilitating treatment of the underlying cause of liver disease as well as the implementation of surveillance for HCC. Screening strategies for cirrhosis should be investigated to determine whether these can reduce overall mortality, including that from HCC.